Genomic Signatures of Adaptation to Stress Reveal Shared Evolutionary Trends Between Tetrahymena utriculariae and Its Algal Endosymbiont, Micractinium tetrahymenae - Kelly, Joseph B; Carlson, David E; Reuter, Manuela; Sommershof, Annette; Adamec, Lubomír; Becks, Lutz (Molecular biology and evolution, 2025)
The evolution of intracellular endosymbiosis marks a major transition in the biology of the host and endosymbiont. Yet, how adaptation manifests in the genomes of the participants remains relatively understudied. We investigated this question by sequencing the genomes of Tetrahymena utriculariae, a commensal of the aquatic carnivorous bladderwort Utricularia reflexa, and its intracellular algae, Micractinium tetrahymenae. We discovered an expansion in copy number and negative selection in a TLD domain-bearing gene family in the genome of T. utriculariae, identifying it as a candidate for being an adaptive response to oxidative stress resulting from the physiology of its endosymbionts. We found that the M. tetrahymenae genome is larger than those of other Micractinium and Chlorella and contains a greater number of rapidly expanding orthogroups. These were enriched for Gene Ontology terms relevant to the regulation of intracellular signal transduction and cellular responses to stress and stimulus. Single-exon tandem repeats were overrepresented in paralogs belonging to these rapidly expanding orthogroups, which implicates long terminal repeat retrotransposons (LTRs) as potential agents of adaptation. We additionally performed a comparative transcriptomic analysis of M. tetrahymenae in a free-living state and in endosymbiosis with T. utriculariae and discovered that the genes that are differentially expressed were enriched for pathways that evidence shifts in energy generation and storage and in cellular protection strategies. Together, our results elucidate the axes along which the participants must adapt in this young endosymbiosis and highlight evolutionary responses to stress as a shared trend.
Keywords: Symbiosis; Evolution, Molecular; molekulární evoluce; fyziologická adaptace; Stress, Physiological; fyziologický stres; Biological Evolution; endosymbiosis; stress; Tetrahymena; symbióza; LTR; ciliate; green algae; biologická evoluce; tandem gene duplications; genome; Adaptation, Physiological